Application of lime pelletted Rhizobium culture for increasing the yield of blackgram (Vigna mungo) in the constrained acidic soils of West Bengal - DAS, INDRANIL; SAHU, NARAYAN CHANDRA; ROY, SUBRATA KR (The Indian Journal of Agricultural Sciences, 2014)
A study was conducted in the Instructional farm of Dakshin Dinajpur Krishi Vigyan Kendra (on-station trial) as well as in the framers’ field (on farm testing) to study the productivity enhancement of Vigna mungo L. in the selected acidic soils of West Bengal. Proper NPK application along with lime pelleted seed treatment with Rhizobium increased the yield by 34.5% over farmers’ practice while addition of lime in soil increased 30% additional yield. In OST and OFT significant productivity increase (94.6% and 64% respectively) in blackgram was achieved through the application of lime, balanced fertilization, Rhizobium seed treatment while best economic returns were obtained through lime pelleted Rhizobium seed treatment in blackgram compared to least management practices.